Studying the Effect of the Energy Settings of the HO-YAG Laser and the Composition of the Stones on the Fragmentation Time in vitro - Ferial.Y. Nazal; Hussein Al Husseini; Hazim R.Akal (University of Thi-Qar Journal of Science, 2022)
Among the many in vitro lithotripsy devices, a holmium-YAG laser lithotripter has been developed to treat urinary tract stones . This research aims to show the effect of the coefficients of the Ho-YAG laser at wavelength 2100 nm on the in vitro fragmentation time and stone composition by checking the stone formation and stabilization of the energy of the pulsed holmium laser while calculating the time required to break the stone . From March 2020 to October 2020, 50 ureteral stone samples were collected from 50 patients (as a result of lithotripsy surgery <10 mm) between the ages of 10-85 years . The patient was treated in the Urology department of Al-Hussein Teaching Hospital by using a Ho-YAG laser radiation wavelength of 2.12 µw, the reaction absorption coefficient 30 cm-1, with a maximum output power of 20 watts, for a laser pulse width of 350 microseconds in an optical fiber with a diameter of 272-550 microns with a power of 0.8 - 1.2 J at 6-8 Hz. The samples obtained are selected groups of stones recovered after lithotripsy. This study showed that the average size of the stones less than 10 mm was 9.5 ± 0.7 mm for the first group of stones of the same composition (calcium oxalate monohydrate), and the mean age of the patients was 31 ± 2.82 years and the time of fragmentation ( 70 ± 1.41) sec, with a pulse energy of 0.8 J with a repetition rate of 6 Hz. The mean age of the patients was 24.5 ± 12.02 years for a mean stone size of 10 ± 1.41 mm with a lithotripsy time (61.5 ± 2.12) s, with a pulse energy of 1.2 J and a repetition rate of 8 Hz. The second group of stones (calcium oxalate dihydrate), the mean age of the patients was 29.5 ± 16.26 years for the mean stone size (7 ± 1.41) mm, and the time to disintegration (57 ± 2.12) seconds, with a pulse energy of 0.8 J and repetition rate of 6 Hz. The mean age of patients was (25 ± 4.24) years for mean stone size (8.5 ± 0.7) mm. Fragmentation time (51 ± 1.41) s with a pulse energy of 1.2 J at a repetition rate of 8 Hz . Group III (uric acid) stones had a mean age of patients (18 ± 2.82) years with a mean stone size of (8.5 ± 0.7) mm and a dissolving time (30 ± 1.41) seconds, with a pulse energy of 0.8 J with a repetition rate of 6 Hz and patients’ mean age (32 ± 4.24) years for mean stone size (8 ± 2.82) mm and disintegration time (20.5 ± 2.12) s, with a pulse energy of 1.2 J at a repetition rate of 8 Hz . Group IV stone (struvite) patients had a mean age of (16 ± 11.31) years with mean stone size (10.5 ± 4.94 mm), mean disintegration time (15 ± 1.41) s, with a pulse energy of 0.8 J at a repetition rate of 6 Hz and a mean​​ Patients’ age (20 ± 10.6) years for mean stone size (9 ± 1.41) mm and fragmentation time (9 ± 1.41) sec, with a pulse energy of 1.2 J at a repetition rate of 8 Hz . The fifth group of stones (cysteine) for the average age of the patients was (37 ± 0) years for the mean stone size (6.5 ± 0.7) mm and disintegration time (89 ± 1.41) seconds, with pulse energy 0.8 J with a repetition rate of 6 Hz and a mean Patients’ age (33 ± 0) years had a mean stone size (7 ± 2.82) mm with a fragmentation time (84 ± 1.41) s, with a 1.2 J pulse energy at an 8 Hz repetition rate. Ho-YAG laser lithotripsy is an excellent treatment method related to the time required for lithotripsy with the type of stones and the different laser settings used .